CHANGES OF mRNA CASPASE-3 AFTER FIRST CYCLE OF CHEMOTHERAPY AS BIOMARKER ASSOCIATE TO CHEMOTHERAPY NEGATIVE RESPONSE IN LOCALLY ADVANCED BREAST CANCER - Widiana, I. K.; Manuaba, I. B. T. Wibawa; Kawiyana, K. Siki; Yasa, I W. P. Sutirta (BALI MEDICAL JOURNAL; Vol 4 No 2 (2015), 2015)
Background: Problems caused by behaviour of biology molecular in locally advanced breast cancer still unpredictable. This study aims to identify the mRNA caspase-3 as a predictive biomarker associated to chemotherapy sensitivity following neoadjuvant chemotherapy (NAC) in patients with locally advanced breast cancer. Methods: Open biopsy before and core biopsy after first cycle neoadjuvant chemotherapy of 62 locally advanced breast cancer patients was analysed for mRNA caspase-3 by Reverse Transcription - Polymerase Chain Reaction (RT-PCR) and this was correlate with response to NAC using American Joint Committee on Cancer (AJCC) creteria. Results: The total mean of mRNA caspase-3 expression before chemotherapy was 12.51±3.03 and after chemotherapy was 11.64±3.13. Negative response to chemotherapy was 44 (70.96%) and positive response was 18 (29.03%). The result of data with Phi and Cramer’s V analysed showed that decrease of mRNA caspase-3 after chemotherapy first cycle as a risk factor to chemotherapy negative response in patients with locally advanced breast cancer was significantly (p = 0.007). Conclusion: Decrease of mRNA caspase-3 after chemotherapy first cycle correlated with chemotherapy negative response in patients with lacally advanced breast cancer.
Keywords: mRNA; caspase-3; neoadjuvant; chemotherapy; locally advanced breast cancer.